Tingkat Pengetahuan Orang Tua dan Tingkat Ketergantungan Gadget pada Anak Usia Sekolah: Level of Parental Knowledge and Level of Gadget Dependence on School-Age Children - Dui Ernawati; Ahmad Rizal; Bambang Suryadi (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: Social media addiction can affect learning achievement in adolescents because good learning achievement can affect a person's academic learning score. Methods: The design of this study used quantitative with cross sectional approach on 60 adolescents using total sampling techniques. Methods by using a standardized questionnaire to measure social media addiction, namely the Social Media Addiction Scale (SMAS) and learning achievement that was tested by the validity of researchers with 19 respondents obtained Cronbach’s Alpha 0,757. The analysis of this study used the chi-square test. Results: This study describes the majority of the frequency distribution of social media addiction as less as 43 respondents and the frequency distribution of good learning achievement of 36 respondents. This study described the relationship between social media addiction with learning achievement in adolescents (p = 0.008). Discussion: There was a correlation between social media addiction with learning achievement in adolescents.